Polarization versus Mori-Tanaka approximations for effective conductivity of isotropic composites - Kien, Nguyen Trung; Chinh, Pham Duc; Duyen, Nguyen Thi Hai (Vietnam Journal of Mechanics, 2018)
Our polarization approximations for the effective conductivity of isotropic multicomponent materials, constructed recently as approximate solutions to the minimum energy principles, are compared with the widely used Mori-Tanaka approximation, derived as an approximate solution of the field equations. The similarities and differences, advantages and disadvantages of both approaches are analysed with illustrating numerical examples.